\[\boxed{\text{549\ (549).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 16 - (6 - 11x)^{2} = 0\]
\[(4 - 6 + 11x)(4 + 6 - 11x) = 0\]
\[(11x - 2)(10 - 11x) = 0\]
\[11x - 2 = 0;\ \ \ \ \ \ \ \ \ 10 - 11x = 0\]
\[11x = 2\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ - 11x = - 10\]
\[x = \frac{2}{11}\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x = \frac{10}{11}\]
\[Ответ:x = \frac{2}{11};\ \frac{10}{11}.\]
\[( - 2m - 32)(16m + 6) = 0\]
\[Ответ:\ x = - 16;\ - \frac{3}{8}.\]
\[\boxed{\text{549.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ y^{2} - 6y = 0\]
\[y \cdot (y - 6) = 0\]
\[y = 0\ \ или\ \ y - 6 = 0\]
\[\text{\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ }y = 6\]
\[Ответ:y = 0;6.\]
\[2)\ x^{2} + x = 0\]
\[x \cdot (x + 1) = 0\]
\[x = 0\ \ или\ \ x + 1 = 0\]
\[\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x = - 1\]
\[Ответ:x = 0;\ - 1.\]
\[3)\ 4m^{2} - 20m = 0\]
\[4m \cdot (m - 5) = 0\]
\[4m = 0\ \ или\ \ m - 5 = 0\]
\[\ \ \ m = 0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ m = 5\]
\[Ответ:m = 0;\ 5.\]
\[4)\ 13x^{2} + x = 0\]
\[x \cdot (13x + 1) = 0\]
\[x = 0\ \ или\ \ 13x + 1 = 0\]
\[\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x = - \frac{1}{13}\]
\[Ответ:x = 0;\ - \frac{1}{13}.\]
\[5)\ 9x^{2} - 6x = 0\]
\[3x \cdot (3x - 2) = 0\]
\[3x = 0\ \ или\ \ 3x - 2 = 0\]
\[\ \ \ x = 0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x = \frac{2}{3}.\]
\[Ответ:x = 0;\frac{2}{3}.\]
\[6)\ 12x - 0,3x^{2} = 0\]
\[0,3x \cdot (40 - x) = 0\]
\[x = 0\ \ или\ 40 - x = 0\]
\[\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x = 40.\]
\[Ответ:x = 0;40.\ \]